Mechanisms for Variability of ZrB2‐30 vol% SiC Oxidation Kinetics. Issue 7 (26th March 2014) - Shugart, Kathleen; Patterson, Brandon; Lichtman, David; Liu, Siying; Opila, Elizabeth; Fahrenholtz, B.
<x xml:space="preserve">Abstract</x> The oxidation kinetics of ZrB2‐30 vol% SiC were analyzed statistically with the goal of understanding the underlying mechanisms for observed variability. A box furnace was used to oxidize specimens for times between 30 s and 100 h at temperatures of 1300°C–1550°C in air. The specimens were characterized to determine weight change, scale thickness, and scale composition to quantify the oxidation behavior. Weight gain measurements of different specimens after 100 min of exposure showed differences of up to 2 mg/cm2 for the same testing conditions where the average weight gain was 2.54 mg/cm2. Variation of 30%–80% was observed in the average thickness of each layer of the oxide within a single specimen. Viscous glass flow was ruled out as a potential mechanism. Glass bubble formation was proposed as the main cause for oxidation kinetics variability.